Collaborative managerial practices of Heads of Educational Institutions: Principals’ and students’ perspective - Syed Manzoor Hussain Shah; Sajjad Hussin (penerbit ukm, 2013)
The study was designed to explore the managerial practices of secondary school principals in collaboration with different school stakeholders i.e. teachers, students and school councils. The population of the study comprised 41 principals of government secondary schools, 249 Secondary school teachers (SSTs), 3360 students of 10th class and 300 members of the school councils of government secondary schools (both boys and girls) in Wazirabad, Pakistan. 50 percentage principals, 40 percentage SSTs, 3 percentage students and 15% members of the school councils were taken as a sample of the study. Data was collected through different four questionnaire design on a five point rating scale. The questionnaires for teachers, students and school councils were developed to see their involvement in school management. The questionnaire for the secondary school principals was designed to find out to see their perceptions about the involvement of these stakeholders in school’s management. The results of the students indicated that, the remaining stakeholders were not cooperating with the school management. It was recommended that all the stakeholders be provided equal opportunities to take an active part in the school management. This may be based on a formal mechanism for the collaborative efforts of all the stakeholders.